Factors influencing on consumer purchase interest through Shopee & Tokopedia study case : book & stationery stores La Tansa Gontor Ponorogo e-commerce - muhammad ridho akbar (NUsantara Islamic Economic Journal, 2023)
The development of information technology is changing many facets of existence. The internet has broad connectivity and reach, low communication costs, is manageable, and swiftly disseminates information because it is so widely used in society. Indeed, the phenomena of internet usage, which is anticipated to grow over time, presents a new economic potential for e-commerce. One of the businesses owned by Pondok Modern Gontor, situated in Ponorogo City, East Java, is La Tansa Gontor Book & Stationery Store. One of several bookstores in Ponorogo Regency is La Tansa Bookstore. Facebook, Whatsapp, and Instagram are all extensively used by La Tansa Bookstore to advertise on social media. To increase consumer reach, it makes use of a number of marketplaces, including Shopee and Tokopedia. For Pondok Modern Darussalam Gontor, using a marketplace as a sales channel is obviously novel, particularly for the La Tansa Gontor Bookstore because not a single business unit has done so, even if selling through the Shopee and Tokopedia platforms has been well-received. The significant level of interest from buyers in many locations speaks to the neighborhood. The increase of Followers and the numerous conversations between clients and the online administrator of La Tansa Bookstore show that the community reacts favorably. The Theory of Planned Behavior, popularized by Icek Ajzen, is the theory applied in this study. This hypothesis is predicated on three different variables: behavioral attitude, subjective norms, and perceived behavioral control. In this study, a descriptive survey method is combined with a quantitative approach. With a sample size of 358 participants, the population in this study consisted of the 3,416 followers in marketplace platform. Several linear regression tests were employed in this investigation. A total score of 31,038 indicated that the aspects of product price and quality were thought to be very influential. The product pricing component, one of the two variables included in the study, had the most significant impact on consumer purchasing interest. with a 66.3% percentage. Product quality, on the other hand, has a 11.48% influence on consumer purchasing interest. Overall, the factors of product price and product quality jointly affect consumer purchasing interest with a significance of 0.05 and a F computed value of 293,715 F table 3.021, indicating that both factors have an impact.